1987
DOI: 10.1017/s0003356100012265
|View full text |Cite
|
Sign up to set email alerts
|

The effect of two concentrations of dietary protein and of formaldehyde-treated soya-bean meal on the performance of high-yielding dairy cows

Abstract: In two experiments, 165 dairy cows were allotted to groups given post-partum diets ad libitum containing either 150 g (LP) or 190 to 200 g (HP) crude protein (CP) per kg dry matter (DM).In experiment 1, which lasted 21 weeks after calving, cows were given pre-partum two amounts of energy (National Research Council (NRC) recommended amount v. 1·4 × NRC recommended amount). Pre-partum amounts of energy did not affect DM intake, milk yield or milk composition. Protein intake, including that for maintenance, was 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Sirohi et al (2013) reported that rumen bypassing of protein fractions (formaldehyde treated mustard cake) showed beneficial effect on milk production without affecting the composition in medium producing crossbred cows fed wheat straw based diets. Similar results were reported by various workers by feeding bypass protein supplements in lactating animals which may be due to increased pool of amino acids at tissue level for utilization (Kaim et al 1987, Hamilton et al 1992, Mishra et al 2006. Feeding formaldehyde protected protein at higher levels in the ration of crossbred cattle (Sampath et al1997, Shelke andThakur 2011) and buffaloes (Chatterjee and Walli 2003) improved the milk yield by 16-20%.…”
Section: Strategic Nutrient Supplementssupporting
confidence: 78%
“…Sirohi et al (2013) reported that rumen bypassing of protein fractions (formaldehyde treated mustard cake) showed beneficial effect on milk production without affecting the composition in medium producing crossbred cows fed wheat straw based diets. Similar results were reported by various workers by feeding bypass protein supplements in lactating animals which may be due to increased pool of amino acids at tissue level for utilization (Kaim et al 1987, Hamilton et al 1992, Mishra et al 2006. Feeding formaldehyde protected protein at higher levels in the ration of crossbred cattle (Sampath et al1997, Shelke andThakur 2011) and buffaloes (Chatterjee and Walli 2003) improved the milk yield by 16-20%.…”
Section: Strategic Nutrient Supplementssupporting
confidence: 78%
“…Mean and median values were similar for all variables in this data set. A significant curvilinear relationship (R 2 = 0.19) was found between milk yield and the concentration of CP All data were taken or calculated from experiments reported in 112 independent studies (Barney et al, 1981;Mielke and Schingoethe, 1981;van Dijk et al, 1983;Henderson et al, 1985;Polan et al, 1985Polan et al, , 1997Van Horn et al, 1985;Broderick, 1986Broderick, , 1992Broderick, , 2003Lundquist et al, 1986;Annexstad et al, 1987;Garnsworthy and Jones, 1987;Howard et al, 1987;Jaquette et al, 1987;Kaim et al, 1987;Bowman et al, 1988;Hadsell and Sommerfeldt, 1988;Jones and Garnsworthy, 1988;Léonard and Block, 1988;Manson and Leaver, 1988;Robinson and Kennelly, 1988;Schingoethe et al, 1988;Sloan and Rowlinson, 1988;Voss et al, 1988;Bruckental et al, 1989Bruckental et al, , 2000De Gracia et al, 1989;Garnsworthy, 1989;Herrera-Saldana and Huber, 1989;Higginbotham et al, 1989;Mä ntysaari et al, 1989;Blauwiekel et al, 1990;Broderick et al, 1990Broderick et al, , 1993Canfield et al, 1990;Casper et al, 1990Casper et al, , 1999…”
Section: Performance Of Lactating Dairy Cowsmentioning
confidence: 99%
“…Cows with negative energy balances may respond more strongly to protected protein (Vérité and Journet 1977, Ahrar and Schingoethe 1979, ORSKOV et al 1981,Kaim et al 1987. In Bertilsson's (1991) experiment, where heat treatment of RSM increased milk yield, restricted feeding resulted in weight loss by the cows.…”
Section: Effect Of Protein Protection On Milk Yield and Protein Contentmentioning
confidence: 99%